Control and management of multicast-capable IP over WDM networks - Chen, Sheng (2010)
Wavelength-routed networks require control and management protocols to perform routing and wavelength assignment (RWA) functions, and exchange signaling information for resource reservations and other network operations. In this thesis, the problems in connection with the control and management of multicast-capable IP over WDM networks are studied. The focus is on investigating the performance of various protocols for dynamic lightpath provisioning, and developing efficient algorithms to improve the performance of multicast-capable IP over WDM networks, in which dynamic traffic grooming, optical multicasting, placement of wavelength converters and light splitters are supported for both unicast and multicast IP traffic. Performances of various control and management protocols for dynamic lightpath provisioning have been studied. The results show that the centralized global information-based link state approach yields the lowest request blocking probability, low control message overhead and low connection setup time. However, when network size is large or the average event processing delay is long, the centralized approach will not be scalable.